SIFAT FISIK OSEANOGRAFI PERAIRAN KEPULAUAN TAMBELAN DAN SEKITARNYA, PROPINSI KEPULAUAN RIAU - Syaifuddin, Syaifuddin (Jurnal Perikanan dan Kelautan, 2010)
Research oceanographie physical properties of sea water has been carried outin Tambelan Islands and surrounding waters on 4-11 November 2010 on twelveoceanographic stations, research using the research vessel KR. Baruna Jaya VIII.Research methods to measure the mass of water using a Conductivity Temperatureand Depth (CTD) 911 plus Model SBE. To measure the current using AcousticDoppler Current Profile (ADCP). The purpose of the study to determine the physicalproperties of oceanography at Tambelan and surrounding waters. From researchresult obtained by the maximum current speed 1606 mm / sec and a minimum of 5mm / sec, with the current direction Southeast 1350, 195-2400 Southwest, Northeastand East 450 30-80-1050. While the maximum temperature of 32.62 °C and 28.59 °Cminimum, maximum salinity of 32.62 per mil and a minimum of 32.01 per mil, amaximum brightness of 97.65% and 70.52% minimum, maximum chlorophyll 0.47mg / l and a minimum of 0, 19 mg / l, and maximum pH of 7.81 and minimum 7.78